Long-term efficacy and safety of bronchial thermoplasty in patients with moderate-to-severe persistent asthma: a systemic review and meta-analysis. (2nd January 2016) - Zhou, Jian Ping; Feng, Yun; Wang, Qiong; Zhou, Li Na; Wan, Huan Ying; Li, Qing Yun
Abstract: Objective : To evaluate the long-term efficacy and safety of bronchial thermoplasty (BT) in the treatment of patients with moderate-to-severe persistent asthma. Methods : We therefore performed a systematic literature review of peer-reviewed studies focusing on BT intervention in asthma control published between January 2000 and June 2014. Three randomized controlled studies and extension studies met the inclusion criteria ( n = 6). Outcomes assessed after BT included spirometric data, adverse respiratory events, emergency room (ER) visits and hospitalization for respiratory illness. One-year and 5-year follow-up data were defined as V1 and V5, respectively. Results : There were 249 BT-treated subjects in total who had a 1-year follow-up (V1), whereas 216 of them finished a 5-year follow-up (V5). No evidence of significant decline was found in pre-bronchodilator FEV1 (% predicted) (WMD = 0.75; 95% CI: 3.36 to 1.85; p = 0.57), or in post-bronchodilator FEV1 (% predicted) (WMD = 0.62; 95% CI: 3.32 to 2.08; p = 0.65) between V1 and V5. In addition, the frequency of respiratory adverse events was reduced significantly during the follow-up (RR = 3.41, 95% CI: 2.96–3.93, p < 0.00001). The number of ER visits for adverse respiratory events remained unchanged (RR = 1.06, 95% CI: 0.77–1.46, p = 0.71) after BT treatment. There was no statistically significant increase in the incidence of hospitalization for respiratory adverse events (V5 vs. V1, RR = 1.47, 95% CI: 0.69–3.12, p = 0.32). Conclusions : These data demonstrate long-term benefits of BT with regard to both asthma control and safety for moderate-to-severe asthmatic patients.